Inferior Oblique Muscle Weakening: Is It Possible to Quantify Its Effects on Horizontal Deviations? - Hande Taylan Sekeroglu; Ozlem Dikmetas; Ali Sefik Sanac; Emin Cumhur Sener; Umut Arslan (Journal of Ophthalmology)
Objective. To evaluate and quantify the effect of inferior oblique muscle weakening on horizontal deviations. Methods. The medical files of patients who had undergone an inferior oblique weakening as a single procedure were all reviewed. The main measures were the type of inferior oblique overaction (IOOA), pre- and postoperative amount of IOOA, and horizontal deviations in primary position. Results. The study was conducted with 66 patients (30 males, 36 females). The median age was 11 years (1–49). Of the 66 patients, 30 (45.5%) had primary and 36 (54.5%) had secondary IOOA. The most common procedure was inferior oblique anteriorization in 32 patients (48.5%). The mean postoperative horizontal and vertical deviations and the amount of IOOA were decreased postoperatively ( for all). The median amount of correction of horizontal near and distance deviations was (0–20). The preoperative amount of IOOA, the presence of fourth nerve palsy, and the type of the weakening procedure had no significant effect on the amount of correction of horizontal deviations. Conclusion. The inferior oblique weakening procedures have secondary effects and warrant reduction of horizontal deviations in varying degrees. This should be borne in mind in planning a simultaneous horizontal muscle surgery and setting the surgical amount.